The Impact of Internet Addiction on Introvert Personality - Nadia Nopiana; Jams Egie; Olir Mers (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
Personality is defined as a combination of the overall disposition with environmental influences. According to some opinions, Personality is divided into two personalities they are extrovert and introvert. A person with an introverted personality tends to be shy, does not talk much and is busy with what is in himself, and tends to be ignorant of others. The tendency of attitudes possessed by an introverted person makes him a careless person in the face of his outside world. The actions carried out by a person with an introverted personality tend to benefit himself and do not attach importance to how others are. Introverted personalities are formed by several things that are done or happen, one of which is Internet Addiction. Seeing the number of things that can be used on the Internet makes use by some people in an excessive way. Individuals who are actually able to interact well in the real world tend to choose to interact through the virtual world because of the convenience offered. As a result, the individual's ability to interact and socialize becomes dulled. The method used is a literature study. As for the purpose of this discussion, in order to be able to anticipate something that has a bad effect on blackness. From the discussion and research results, it can be concluded that there is a relationship or influence between Internet Addiction on Introverted Personality.